Ecological and Economical Friendly Analysis of A Hybrid Solar-Grid-Diesel Connected Power Generation System - Rafat Qonain; Malik Rafi; Imran Khan; Shivley Sageer (International Journal of Applied Power Engineering (IJAPE), 2018)
This paper presents Importance of hybrid power system. This paper depicts model and simulation of a renewable energy based hybrid power system for improving power quality because optimal utilization of primary energy sources will increase the level of supply reliability. The combination of Grid, Photo Voltaic (PV) Array System, and Diesel generator systems are used for power generation. Due to variation in output power of solar panel, Diesel engine is also coupled to ensure reliable supply under all conditions. The results shows that the proposed hybrid power system can effectively manage the optimal utilization of primary energy sources and improves the power quality in an islanding as well as grid connected mode.